2022
DOI: 10.3390/mi14010041
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Electrochemical Microsensors for Ascorbic Acid Detection: Clinical, Pharmaceutical, and Food Safety Applications

Abstract: Nowadays, micro-sized sensors have become a hot topic in electroanalysis. Because of their excellent analytical features, microelectrodes are well-accepted tools for clinical, pharmaceutical, food safety, and environmental applications. In this brief review, we highlight the state-of-art electrochemical non-enzymatic microsensors for quantitative detection of ascorbic acid (also known as vitamin C). Ascorbic acid is a naturally occurring water-soluble organic compound with antioxidant properties and its quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Figure B showed that there was a linear relationship in the concentration range of AA from 150 to 500 μM; the limit of detection (LOD) was calculated to be 9.3 μM. The linear range of AA detection well-covered the physiological concentration of AA in the living brain . Then, we further explored the stability of the CFE/CNT –COOH /PEDOT electrodes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure B showed that there was a linear relationship in the concentration range of AA from 150 to 500 μM; the limit of detection (LOD) was calculated to be 9.3 μM. The linear range of AA detection well-covered the physiological concentration of AA in the living brain . Then, we further explored the stability of the CFE/CNT –COOH /PEDOT electrodes.…”
Section: Resultsmentioning
confidence: 97%
“…The linear range of AA detection well-covered the physiological concentration of AA in the living brain. 61 Then, we further explored the stability of the CFE/CNT −COOH /PEDOT electrodes. As demonstrated in Figure 3C, the CFE/ CNT −COOH /PEDOT electrode was so stable that the current decreased by only 4% after continuous DPV scanning for 300 cycles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…AA plays an important role in many physiological processes and is associated with numerous diseases . Establishing reliable, sensitive, and selective assays to accurately quantify AA is significant for clinical diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…AA plays an important role in many physiological processes and is associated with numerous diseases. 47 Establishing reliable, sensitive, and selective assays to accurately quantify AA is significant for clinical diagnosis. Because of the unique PL and oxidase-like activity switching behaviors of CePO 4 :Tb@MnO x , which can be adjusted by the synergistic regulatory mechanism through specific redox reactions (KMnO 4 for oxidation and AA for reduction), a dual-mode colorimetric/fluorometric assay of AA was established.…”
Section: Effect Of Aa On the Pl Andmentioning
confidence: 99%
“…Electrochemical techniques have advantages over other techniques such as spectrometry and chromatography in food, biological, pharmaceutical, and clinical applications. These include high precision and sensitivity, selectivity, cost effectiveness, defined reaction time, environmentally friendly, miniaturization, and minimum sample pretreatment [ 1 , 2 ]. Nanomaterials have been extensively used to develop advanced electrochemical sensors and biosensors for a wide range of applications [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%